The dragon prophecy the fourth adventure in the Kingdom of Fantasy - Stilton, Geronimo; Barozzi, Danilo; Bigolin, Silvia; Giundani, Giuseppe; Heim, Julia (New York, N.Y. Scholastic Inc., 2012)
Princess Sterling sends the Dragon of the Rainbow and Scribblehopper to bring Geronimo Stilton back the the Kingdom of Fantasy, because he is the hero in the dragon prophecy who will find the stolen dragon egg and restore harmony to the kingdom.
"Original title Quarto Viaggo nel Regno della Fantasia"--T.p. verso.
007-010.
RL3.
Keywords: Stilton, Geronimo -- Juvenile fiction; Mice -- Juvenile fiction; Dragons -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Mice -- Fiction; Dragons -- Fiction; Adventure and adventurers -- Fiction; Adventure fiction